St. Margaret's Church, Finglas, door jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
Jamb arch and hood moulding. From intrados, jamb moulding comprises:quadrant, hollow chamfer, quadrant. The splayed jamb and hood are separated by a small hollow. The hood, from outside in, comprises: angle-fillet, angle-fillet, angle-fillet, angle-fillet.
Door
Keywords: quadrant; Architecture, Gothic -- Ireland; Dublin (County); Gothic doorways; Late Medieval; fillets (moldings); roll moldings; hood moldings; moldings, hollow